The association between migraine and hospital readmission due to pain after surgery: A hospital registry study. (February 2019) - Platzbecker, Katharina; Zhang, Megan Behua; Kurth, Tobias; Rudolph, Maira Isabella; Eikermann-Haerter, Katharina; Burstein, Rami; Eikermann, Matthias; Houle, Timothy
Background: Migraine has been identified as a risk factor of 30-day hospital readmission after surgery. We aimed to further characterize this association examining pain as a potentially migraine-associated, preventable reason for readmission. Hypothesis: Compared to patients with no migraine, surgical patients with migraine are at increased risk of 30-day hospital readmission with an admitting diagnosis specifying pain. Methods: This hospital registry study examined 150, 710 patients aged 18 years and above, who underwent surgery with general anesthesia and mechanical ventilation between 2007 and 2015 at a tertiary care center and two affiliated community hospitals in Massachusetts, USA. Results: Migraine was associated with an increased risk of 30-day pain-related readmission after surgery (adjusted odds ratio 1.42 [95% confidence interval 1.15–1.75]). The association was stronger for migraine with aura (compared to migraine without aura: Adjusted odds ratio 1.69 [95% confidence interval 1.06–2.70]; compared to no migraine: Adjusted odds ratio 2.20 [95% confidence interval 1.44–3.37]). The predicted adjusted risk of pain-related 30-day readmissions was 9.1 [95% confidence interval 5.3–13.0] in 1000 surgical patients with migraine with aura and 5.4 [95% confidence interval 4.2–6.6] in 1000 patients with migraine without aura, compared to 4.2 [95% confidence interval 3.8–4.5] in 1000 patients with no migraine. Furthermore, migraine was associated with an increased risk of postsurgical 30-day readmission due to a priori defined migraine-related pain (headache or abdominal pain) (adjusted odds ratio 1.55 [95% confidence interval 1.20–2.00]). Conclusion: Patients with migraine undergoing surgery are at increased risk of 30-day hospital readmission due to pain.